Investigation of printable threshold overhang angle in extrusion-based additive manufacturing for reducing support waste. Issue 10 (3rd October 2018) - Jiang, Jingchao; Stringer, Jonathan; Xu, Xun; Zhong, Ray Y.
ABSTRACT: Notwithstanding the widespread use and large number of advantages over traditional subtractive manufacturing techniques, the application of additive manufacturing technologies is currently limited by undesirable support material waste. Support structures are unavoidable when manufacturing objects with overhangs in extrusion-based Additive manufacturing, leading to extra build time and material waste. In a manufacturing process, different parameters such as cooling fan speed, print speed and print temperature can make a great contribution to printable overhang angle size. In this study, effects of these parameters on printable overhang angle size are studied theoretically and experimentally. First, theoretical analysis of printable overhang is conducted. Then experiments of overhangs with 20°, 30°, 40° and 50° are carried out with regard to different parameters on an FDM printer. According to the results, the printable threshold overhang angle varies substantially with printing conditions. The findings of this paper can then be applied for setting a lower threshold overhang angle for reducing support waste in the future. The findings can also provide some reference for future research in high-precision printing by adjusting relevant print parameters.